The Impact of Playing on the Well-Being of Hospitalized Children - Claudia Mussa; Fani Eta Korn Malerbi (Psicologia, 2008)
The hospitalization for children can be considered a stress situation. Many groups have used interventions to change the mood of hospitalized children. The objective of this study was to assess the impact of playing promoted by a group of story tellers (contadores de histórias), on the hospitalized children emotional state and on pain complaining. Fifteen children with cancer were observed, with the aid of a behavioral ckeck-list. Besides, the children were asked to classify their pain in a Pain Scale and their parents were interviewed before and after the story tellers ́ visit. The results showed that, after the story tellers ́ visit, the majority of children talked more than before; they reduced their pain complaining and became more calm during the medical procedures. These children increased their mobilities in the ward, and their appetite was better than before the story tellers ́ visit. These data show the positive effects of playing.